2011
DOI: 10.1016/j.labeco.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Mixing the princes and the paupers: Pay and performance in the National Basketball Association

Abstract: Abstract:We investigate how team and individual performances of players in the National Basketball Association respond to variations in intra-team pay inequality. By breaking down team dispersion into conditional and expected components, we find that expected pay dispersion has a positive effect on team and individual performance. We find that team and individual performances are essentially orthogonal to conditional pay inequality, counter to the hypotheses of fairness and cohesion proposed in the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 31 publications
0
32
1
Order By: Relevance
“…Thus, overcoming some of the analytical problems, the DeBrock et al (2004) findings reported very similar estimates of a negative relationship between pay dispersion and team performance in the baseball context. Simmons & Berri (2011) conducted an additional analysis in the NBA to overcome the residual dispersion issue and other limitations. Although focused on individual player performance and not team wins as an outcome, they constructed a measure of justified inequality, or the amount of dispersion that could be reasonably explained by existing player talents, as well as a measure of unjustified inequality.…”
Section: Team Performancementioning
confidence: 99%
“…Thus, overcoming some of the analytical problems, the DeBrock et al (2004) findings reported very similar estimates of a negative relationship between pay dispersion and team performance in the baseball context. Simmons & Berri (2011) conducted an additional analysis in the NBA to overcome the residual dispersion issue and other limitations. Although focused on individual player performance and not team wins as an outcome, they constructed a measure of justified inequality, or the amount of dispersion that could be reasonably explained by existing player talents, as well as a measure of unjustified inequality.…”
Section: Team Performancementioning
confidence: 99%
“…Therefore, the presence of tie-hirings is correlated with a general measure of roster stability. Simmons and Berri (2011) recently found evidence for a positive effect of roster stability on player performance in the NBA. They argued that continuous interactions of a stable group of players incorporate learning and peer effects.…”
Section: Resultsmentioning
confidence: 98%
“…This idea is forwarded by Rosen (1981) who observes the "superstar" effect and that wide variation in salaries is important in team success. Simmons and Berri (2011) examine the salary structure of the National Basketball Association (NBA) and also conclude that increased pay inequality enhances player performance and increases the probability of success. However, this research of pay inequality in sports is not uniformly consistent.…”
Section: Literature Reviewmentioning
confidence: 99%